ChemInform Abstract: Synthetic Strategy and Therapeutic Utility of Oxygen and Nitrogen Containing Heterocyclic Compounds. Issue 10 (March 2015) - Joseph, Lincy; George, Mathew; Surekha, S. R.
Abstract Review: 38 refs.